Anxiety in adolescent epilepsy. A clinimetric analysis. (17th August 2016) - Carrozzino, Danilo; Marchetti, Daniela; Laino, Daniela; Minna, Maria; Verrocchio, Maria Cristina; Fulcheri, Mario; Verrotti, Alberto; Bech, Per
Abstract: Background Anxiety and depression have been considered to be neglected disorders in epilepsy. Because panic disorder is one of the most important anxiety disorders, it has been problematic to use very comprehensive anxiety questionnaires in epilepsy patients, as panic attacks and epileptic seizures, although two distinct clinical entities from a diagnostic point of view, show a significant overlap of symptoms. Aims We have focused on single items for anxiety and depression as screening candidates in adolescent epilepsy. Methods The individual panic attack item in the Screen for Children Anxiety Related Emotional Disorders Scale (SCARED) and the single depression item in the Kellner Symptom Questionnaire were tested. Our samples consisted of adolescent patients with epilepsy and a matched control group with healthy participants, as well as two numerical groups acting as controls. Results The single panic attack item identified panic anxiety in 24.1% in the group of patients with epilepsy and 0.0% in the matched control group ( p = 0.01). The single depression item identified 52.2% with depression in the epilepsy group and 6.2% in the matched control group ( p = 0.001). Conclusion As screening instruments, single items of panic attack and depression are sufficient to screen for these affective states in adolescent epilepsy. The clinical implications are that it is important to be quite specific when screening for depression and panic attacks in adolescent patients with epilepsy.